2019
DOI: 10.9734/ajrimps/2019/v8i1-230131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aqueous Extract of Zingiber officinale (Ginger) on Some Biochemical Parameters in Streptozotocin-induced Diabetes Rats

Abstract: Background: Appreciable number of medicinal plants are used for the treatment of diabetes in Nigeria. Aim of the Study: The present study aimed to investigate the antidiabetic activity of Zingiber officinale extracts and its potential mechanisms in streptozotocin-induced diabetic rats. Methodology: Albino rats of Wistar strain weighing between 130 g to 160 g were induced with single freshly prepared streptozotocin (55 mg/kg body weight). Diabetes was confirmed after forty eight hours in streptozotocin -induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 2 publications
3
10
0
Order By: Relevance
“…The reduction of TC and TG were also reported by 15 [ 21 , 26 , 29 , 30 , 34 , 35 , 38 , 41 , 44 , 49 , 52 , 54 , 56 , 59 , 60 ] and 14 [ 21 , 26 , 29 , 30 , 34 , 35 , 38 , 41 , 44 , 49 , 52 , 56 , 59 , 60 ] studies respectively. Ginger has been shown to improve low-density lipoprotein-cholesterol (LDL-C) [ 26 , 29 , 30 , 35 , 38 , 52 , 54 , 56 , 59 ] and high-density lipoprotein-cholesterol (HDL-C) [ 26 , 29 , 30 , 35 , 38 , 49 , 56 , 59 , 60 ] levels in nine studies. One study reported contradictory results for TC, TG, and LDL-C, as well as two studies for HDL-C [ 23 , 44 ].…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…The reduction of TC and TG were also reported by 15 [ 21 , 26 , 29 , 30 , 34 , 35 , 38 , 41 , 44 , 49 , 52 , 54 , 56 , 59 , 60 ] and 14 [ 21 , 26 , 29 , 30 , 34 , 35 , 38 , 41 , 44 , 49 , 52 , 56 , 59 , 60 ] studies respectively. Ginger has been shown to improve low-density lipoprotein-cholesterol (LDL-C) [ 26 , 29 , 30 , 35 , 38 , 52 , 54 , 56 , 59 ] and high-density lipoprotein-cholesterol (HDL-C) [ 26 , 29 , 30 , 35 , 38 , 49 , 56 , 59 , 60 ] levels in nine studies. One study reported contradictory results for TC, TG, and LDL-C, as well as two studies for HDL-C [ 23 , 44 ].…”
Section: Resultssupporting
confidence: 52%
“…Twenty-eight of 31 studies showed that ginger intake lowers blood glucose levels [ 24 , 25 , 27 , 29 , 30 , 34 – 43 , 47 – 49 , 51 – 53 , 55 – 61 ]. On the contrary, in 2 studies, blood glucose levels increased [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…In all studies the impact of ginger on the antioxidant defense system was evaluated, positive results were found. In all studies, ginger elevated the level of GSH [15,19,20,24,28,29,36,49,50], CAT, SOD [15,22,24,36], GR [24,28], GPx [19,22,24,28] and TAC [38,40,53,57] factors. Similarly 2 studies reported that administration of ginger decreased ROS levels [24,50].…”
Section: Ginger and Oxidative Stress Indices In Dkdmentioning
confidence: 96%
“…On the contrary, creatinine levels were increased in one study [32] and not changed in 3 studies [18, 47,53]. Ginger decreased serum levels of urea, BUN, and uric acid in 13 [15-17, 19-21, 23, 29, 30, 34, 36, 47, 53], 6 [15,18,22,24,49,50], and 6 [17,20,22,29,30,43] studies, respectively. On the contrary, urea and uric acid levels were increased in one study [33].…”
Section: Ginger and Function In Dkdmentioning
confidence: 99%
See 1 more Smart Citation